2016
DOI: 10.3389/fendo.2016.00004
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Camel Milk on Insulin Receptor Signaling – Toward Understanding the Insulin-Like Properties of Camel Milk

Abstract: Previous studies on the Arabian camel (Camelus dromedarius) showed beneficial effects of its milk reported in diverse models of human diseases, including a substantial hypoglycemic activity. However, the cellular and molecular mechanisms involved in such effects remain completely unknown. In this study, we hypothesized that camel milk may act at the level of human insulin receptor (hIR) and its related intracellular signaling pathways. Therefore, we examined the effect of camel milk on the activation of hIR tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
57
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 36 publications
(57 reference statements)
11
57
2
Order By: Relevance
“…Regarding the molecular mechanisms responsible for the hypoglycemic action of camel milk, Abdulrahman et al (2016) have recently shown that camel milk has direct effect on insulin receptor conformation and activation, with differential effects on intracellular signaling, enhancing glucose uptake by insulin-sensitive tissues. Furthermore, immunoglobulin antibodies in camel milk may induce immunoregulatory cells that can downregulate the immune system and β-cell salvage (Baheti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the molecular mechanisms responsible for the hypoglycemic action of camel milk, Abdulrahman et al (2016) have recently shown that camel milk has direct effect on insulin receptor conformation and activation, with differential effects on intracellular signaling, enhancing glucose uptake by insulin-sensitive tissues. Furthermore, immunoglobulin antibodies in camel milk may induce immunoregulatory cells that can downregulate the immune system and β-cell salvage (Baheti et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, immunoglobulin antibodies in camel milk may induce immunoregulatory cells that can downregulate the immune system and β-cell salvage (Baheti et al, 2014). Therefore, some investigators have proposed the immunomodulatory theory in explaining the health benefits of camel milk in diseases with an immunologic background, including diabetes mellitus (Abdulrahman et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Agrawal et al [ 50 ] have reported that the half cysteine rich protein in camel milk [ 51 ] is similar to the insulin family proteins and may be attributed for the glycemic control of camel milk for diabetic patients. Abdulrahman et al [ 52 ] demonstrated that an allosteric effect of camel milk on insulin receptor conformation and activation on the intracellular signaling process may be responsible for the antidiabetic properties of camel milk.…”
Section: Functional Potential Of Camel Dairy Productsmentioning
confidence: 99%
“… 13 Camel milk (CAM) showed a unique chemical composition and possess therapeutic activities in treatment of diabetes, and autoimmune disorders such Crohn’s disease, multiple sclerosis and autism. 14 17 In addition, CAM induces protective activity against hepatotoxicants and diverse carcinogens. 18 On the other hand, CAM ameliorates the inflammatory responses and oxidative stress via downregulation of mitogen-activated protein kinase (MAPK) signalling pathways.…”
Section: Introductionmentioning
confidence: 99%